ON THE ISSUE OF THE FREQUENCY OF SPINAL CORD TUMORS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The incidence of spinal cord tumors increases to 3-4% due to improved diagnostics and increased patient referrals to neurosurgical hospitals. The ratio of spinal cord and brain tumors is 1:9. Spinal cord tumors most often occur at the age of 30-40 years.